FIGURES OF SPEECH IN MELENGKAN OF GAYO WEDDING - Pindra Ramadani; Jumino Suhadi; M. Manugeren (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Melengkan is a custom in the plateau of Gayo performed at a wedding expressed in poetical, lyrical or proverbial form.  The study is aimed at identifying the types and uses of figures of speech in Melengkan of   Gayo wedding supported by the concept of figures of speech proposed by Kosasih (2007). The data were collected through observation and a video-recording of the traditional Gayo wedding. as well as interviews with melengkan performers under descriptive qualitative method (Best, 1982). The figures of speech used in Melengkan also reflect the cultural value of Gayo community with points of local wisdom. The findings showed that there were four classifications of figures of speech: Comparison, Substitution, Addition or Amplification, and Omission or suppression used in Melengkan.  The cultural values of Melengkan are for remembrance of local wisdom, warnings from customary philosophy, religion, and also for giving advice and recalling the history and beauty of Melengkan speech. The context of using Melengkan is to perpetuate and reflect cultural values, namely, politeness, respect, speaking softly, friendliness and resoluteness. These findings imply the importance of conserving Melengkan as a part of the Gayo culture in every part of life.